2011
DOI: 10.1108/13639511111157546
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between stress, strain and social capital

Abstract: This paper analyzes the effectiveness of social capital in reducing the negative externalities associated with stress, as well as the physical and psychological strain indicators among police officers. Despite the fact that there is a large multidisciplinary literature on stress or on social capital, the link between both factors is still underexplored. In this empirical paper we therefore aim at reducing such a shortcoming. We focus on a strategically important work environment, namely law enforcement agents,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 82 publications
3
23
0
Order By: Relevance
“…Table 3 shows the result of Pearson correlation analysis and descriptive statistics. The means for the variables are from 4.2 to 4.3 signifying that the levels of PHS, PSS and JOP ranging from high (4) to highest level (7). The correlation coefficients for the relationship between the independent variable (i.e., PHS and PSS) and the dependent variable (i.e., JOP) were less than 0.90, indicating the data were not affected by serious collinearity problem [36].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Table 3 shows the result of Pearson correlation analysis and descriptive statistics. The means for the variables are from 4.2 to 4.3 signifying that the levels of PHS, PSS and JOP ranging from high (4) to highest level (7). The correlation coefficients for the relationship between the independent variable (i.e., PHS and PSS) and the dependent variable (i.e., JOP) were less than 0.90, indicating the data were not affected by serious collinearity problem [36].…”
Section: Resultsmentioning
confidence: 98%
“…In an organizational context, eustress is often called as positive stress where individuals who have adequate knowledge, skills, abilities and attitudes to cope with their work demands and pressures. [4] [5] [6] [7]. On the other hand, distress is also known as negative stress where individuals have not adequate knowledge, skills, abilities and attitudes to cope with external forces and challenges placed on their bodies [3][4] [8].…”
Section: Introductionmentioning
confidence: 99%
“…[ 50 ] Furthermore, Gächter et al found, by analyzing survey data from police officers to assess the relationship between stress, strain, and social capital, that an increase in social capital is significantly correlated to a decrease in perceived level of strain and psychological burnout, thus recommending that stress reduction programs should actively engage employees to build stronger social relations and networks. [ 51 ]…”
Section: Discussionmentioning
confidence: 99%
“…eustress and distress conditions (Selye, 1987;Ismail, Yao, Lai-Kuan & Soon-Yew, 2010). In an organizational context, eustress is often called positive stress which is beneficial for organizations where individuals have adequate knowledge, skills, abilities and attitudes to cope with their work demands and pressures (Keshavarz & Mohammadi, 2011;Yu-Fei, Ismail, Ahmad, & Kuek, 2012;Code & Langan-Fox, 2001;Gachter, Savage, & Torgler, 2011). On the other hand, distress is perceived as negative stress refering to individuals having no such positive attributes to cope with external forces and challenges placed on them (Ismail, et.…”
Section: Literature Reviewmentioning
confidence: 99%